MCTS Windows SharePoint services 3.0 configuration study guide - Miller-White, Marilyn; Stork, Paul, 1952-; Wagner, Kris, 1974-; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2009)
"Windows SharePoint Services 3.0 is a free collaborative tool that allows you to share and organize documents, contacts, and calendars; create polls; moderate the content of lists and share libraries; and more. Exam 70-631 tests your knowledge of SharePoint Services 3.0 and this book sharpens your skills as you prepare to take Exam 70-631. Packed with chapter review questions, real-world scenarios, and hands-on exercises, this study guide also readies you for specific aspects of Exam 70-631, including: deploying Windows SharePoint Services 3.0, monitoring SharePoint Services, configuring security for SharePoint Services, administering SharePoint Services, managing customization, and configuring network infrastructure for SharePoint Services"--Resource description page.
Description based on print version record.
"Exam 70-631"--Cover.
Includes index.
Keywords: Intranets (Computer networks) -- Examinations -- Study guides; Microsoft SharePoint (Electronic resource) -- Examinations -- Study guides; Web servers -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books